Experimental Investigation on Geopolymer Concrete with Various Sustainable Mineral Ashes - Avudaiappan-, S (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The aim of this research was to find the best alternative for river sand in concrete. In both geopolymer concrete (GPC) and cement concrete (CC), the fine aggregates are replaced with various sustainable mineral ashes, and mechanical and durability tests are conducted. Specimens for tests were made of M40 grade GPC and CC, with five different soil types as river sand substitute. The materials chosen to replace the river sand are manufactured sand (M-sand), sea sand, copper slag, quarry dust, and limestone sand as 25%, 50%, 75%, and 100%, respectively by weight. GPF50 and CC50 were kept as control mixes for GPC and CC, respectively. The test results of respective concretes are compared with the control mix results. From compressive strength results, M-sand as a fine aggregate had an increase in strength in every replacement level of GPC and CC. Additionally, copper slag is identified with a significant strength reduction in GPC and CC after 25% replacement. Copper slag, quarry dust, and limestone sand in GPC and CC resulted in considerable loss of strength in all replacement levels except for 25% replacement. The cost of GPC and CC is mixed with the selected fine aggregate replacement materials which arrived. Durability and cost analyses are performed for the advisable mixes and control mixes to have a comparison. Durability tests, namely, water absorption and acid tests and water permeability and thermal tests are conducted and discussed. Durability results also indicate a positive signal to mixes with M-sand. The advisable replacement of river sand with each alternative is discussed. © 2021 by the authors. Licensee MDPI, Basel, Switzerland.